Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences